E1A can provoke G1 exit that is refractory to p21 and independent of activating cdk2. - Akli,S; Zhan,S; Abdellatif,M; Schneider,MD (Circ Res, 1999)
E1A can evoke G1 exit in cardiac myocytes and other cell types by displacing E2F transcription factors from tumor suppressor "pocket" proteins and by a less well-characterized p300-dependent pathway. Bypassing pocket proteins (through overexpression of E2F-1) reproduces the effect of inactivating pocket proteins (through E1A binding); however, pocket proteins associate with a number of molecular targets apart from E2F. Hence, pocket protein binding by E1A might engage mechanisms for cell cycle reentry beyond those induced by E2F-1. To test this hypothesis, we used adenoviral gene transfer to express various E2F-1 and E1A proteins in neonatal rat cardiac myocytes that are already refractory to mitogenic serum, in the absence or presence of several complementary cell cycle inhibitors-p16, p21, or dominant-negative cyclin-dependent kinase-2 (Cdk2). Rb binding by E2F-1 was neither necessary nor sufficient for G1 exit, whereas DNA binding was required; thus, exogenous E2F-1 did not merely function by competing for the Rb "pocket." E2F-1-induced G1 exit was blocked by the "universal" Cdk inhibitor p21 but not by p16, a specific inhibitor of Cdk4/6; p21 was permissive for E2F-1 induction of cyclins E and A, but prevented their stimulation of Cdk2 kinase activity. In addition, E2F-1-induced G1 exit was blocked by dominant-negative Cdk2. Forced expression of cyclin E induced endogenous Cdk2 activity but not G1 exit. Thus, E2F-1-induced Cdk2 function was necessary, although not sufficient, to trigger DNA synthesis in cardiac muscle cells. In contrast, pocket protein-binding forms of E1A induced G1 exit that was resistant to inhibition by p21, whereas G1 exit via the E1A p300 pathway was sensitive to inhibition by p21. Both E1A pathways-via pocket proteins and via p300-upregulated cyclins E and A and Cdk2 activity, consistent with a role for Cdk2 in G1 exit induced by E1A. However, p21 blocked Cdk2 kinase activity induced by both E1A pathways equa